PENGARUH KECERDASAN EMOSIONAL AUDITOR TERHADAP KINERJA AUDITOR PADA KANTOR INSPEKTORAT KABUPATEN KONAWE KEPULAUAN - Abdullah, Rudi (JITAA : Journal Of International Taxation, Accounting And Auditing, 2022)
This study aims to determine the effect of auditor's emotional intelligence on auditor performance at the Konawe Kepulauan Regency Inspectorate Office. The data was collected using a questionnaire. Data obtained from 30 people. Data analysis used simple linear regression. The results of the analysis show (R2) = 0.734 which means that 73.4% of the variation of the increase in Auditor Emotional Intelligence on Auditor Performance (X) and the remaining 26.6% is influenced by other variables outside the model, so it can be concluded that the effect of Auditor Emotional Intelligence on Performance The auditor's influence is strong. The correlation coefficient value of 0.857 means that there is a positive relationship between Auditor Emotional Intelligence and Auditor Performance, where the lending variable has a significant value of 0.000 which is smaller than a = 0.05. Thus the research hypothesis is accepted.